2017
DOI: 10.14687/jhs.v14i4.5024
|View full text |Cite
|
Sign up to set email alerts
|

Solution focused thinking in education faculty students<p>Eğitim fakültesi öğrencilerinde çözüm odaklı düşünme ve empati

Abstract: This research was conducted to examine the solution-focused thinking and empathy levels of the faculty of education students. The study group consists of 253 students (184 females, 69 males). Findings show that there is a significant relationship between the solution-focused thinking (problem disengagement, resource activation, goal-orientation) and empathy levels (social skills, emotional reactivity, cognitive empathy) of the students. On the other hand, significant differences are found in the solution-focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In a study conducted with pre-pandemic education faculty students in Turkey, the SFT skills of students were at a medium level (SHI, 50.3 ± 7.71) (14), which is similar to the result of this study (49.63 ± 5.72). Unlike other university students, midwifery students receive practical training, including clinical practice (based on skills) and theoretical training (22,23).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In a study conducted with pre-pandemic education faculty students in Turkey, the SFT skills of students were at a medium level (SHI, 50.3 ± 7.71) (14), which is similar to the result of this study (49.63 ± 5.72). Unlike other university students, midwifery students receive practical training, including clinical practice (based on skills) and theoretical training (22,23).…”
Section: Discussionsupporting
confidence: 85%
“…Few studies have been found to determine the SFT disposition and/or hope levels of students in our country. According to a study conducted with students from the faculty of education, the SFT skills of female students were at a higher level (14). Bilgiç et al (15) found that nursing stu-dents and Duman et al (16) found that university students have high levels of hope.…”
Section: Introductionmentioning
confidence: 99%